(untitled) (Bangladesh Journal of Medical Science, 2026)
Background Predictors of stroke outcomes are still poorly understood. In the Kazakh scientific literature, there are only some works considering the determinants of stroke outcomes, despite the high prevalence of this disease. Objectives The aim of the study was to analyze the influence of risk factors on the annual survival of stroke patients in the population of residents of the Aktobe region. Methods The cohort study included all cases of cerebral strokes in Aktobe from 01.01.2021 to 01.01.2022(n=754). The survival rate of patients with MI was assessed using the Kaplan-Mayer method with the determination of the difference between the groups using a log-rank criterion. To assess the independent influence of forecast factors on annual mortality, a multidimensional analysis of proportional Coke risks was used. Adjusted relative risks (RR) were calculated with 95% confidence intervals (CI). Results Based on the results obtained, it can be assumed that the one-year survival rate is 24.8%, and the median survival rate of 40 days is 95% CI (25.9 - 54.1), which does not differ significantly in survival in developed countries. The factors influencing the annual survival of patients with cerebral strokes in Kazakhstan have been determined. Gender, age, hospitalization time and severity of stroke on the GCS scale are closely related to survival at 12 months. Conclusions The factors influencing the annual survival rate of stroke patients in Kazakhstan have been identified. These results can be used to develop treatment and rehabilitation strategies aimed at improving long-term outcomes in stroke patients. BJMS, Vol. 25 No. 02 April’26 Page: 609-614